How & why?: Third-person perceptions of people with terminal illnesses’ suicides as a function of suicide method & motive - Schiffer, Ashley A. (My University, 2025)
Suicide and terminal illness are two phenomena that are stigmatized independently of one another (e.g., Batterham et al., 2013; Epley & McCaghy, 1978). However, suicide by people with severe physical health states is perceived fairly positively in general (e.g., Schiffer & Saucier, 2024) as well as more acceptable compared to suicides precipitated by other situations (e.g., interpersonal issues; Winterrowd et al., 2015). For further insight on the coexistence of suicide and terminal illness, this research quantitatively assessed how third-person perceptions of people with terminal illnesses’ suicides (e.g., acceptability, stigma) vary as a function of situational factors related to the suicide as well as individual differences among participants related to pride and existential considerations. Vignettes were used in between-groups designs to manipulate situational factors including a target person’s suicide method (Study 1) and primary motive (Study 2). On average, participants reported generally favorable attitudes toward this phenomenon across studies. In Study 1, medical methods (e.g., physician-assisted death) were perceived more favorably than traditional methods (e.g., hanging), but minimal differences in perceptions emerged across various suicide motives (e.g., mental health concerns, wanting control over death) in Study 2. Masculine Honor Beliefs were positively associated with stigmatizing attitudes toward the target. The effects of Free Will Beliefs were often moderated by the conditional manipulations. Self-directed and other-directed Fear of Death yielded contradictory effects. Suicide Acceptability was consistently positively associated with favorable attitudes toward this phenomenon. Overall, this program of research has important implications for understanding nuances in third-person perceptions of this phenomenon as a function of relevant situational factors (e.g., method, motive) and individual differences, while advancing suicide theories to be more comprehensive and inclusive of severe physical health states.
Keywords: Suicide; Terminal illness; Masculine honor beliefs; Free will beliefs; Fear of death; Suicide acceptability